Criterios de graduación de las faltas disciplinarias en el régimen especial para las FF.MM y su comparación con el régimen disciplinario ordinario (2013)
In order to meet goals of the State, the law provides for disciplinary sanctions on public servants that affect the smooth running of the administration, so it is of great importance to the when establishing disciplinary sanctions for committing offenses disciplinary very serious, serious on mirror in law 836 of 2003, consider aggravating mitigating criteria for conduct, degree of involvement in the service and others, as required by law 734 of 2002, not to undermine legal certainty, legality due process.